From Nasal Vestibulitis to Maxillofacial Abscess: Reconstruction of Extensive MRSA-Induced Defects in a Diabetic Patient - Clarissa Fiolly Refieska; Al Hafiz (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2026)
Background: Nasal vestibulitis is frequently regarded as a benign localized infection. However, in immunocompromised hosts, specifically those with uncontrolled diabetes mellitus, it can rapidly escalate into a life-threatening maxillofacial abscess involving the danger triangle of the face. The synergistic destructive potential of Methicillin-resistant Staphylococcus aureus (MRSA) and hyperglycemia poses a formidable challenge for reconstructive surgery due to extensive tissue necrosis and compromised microvasculature. This study evaluates the efficacy of a dual-flap approach—combining Rotation and V-Y Advancement flaps—for restoring extensive midfacial defects. Case presentation: A 51-year-old male with uncontrolled Type 2 Diabetes presented with a massive, ruptured maxillofacial abscess originating from neglected nasal vestibulitis exacerbated by rhinotillexomania. The infection resulted in extensive necrosis spanning the nasal dorsum, infraorbital regions, and forehead. Microbiological analysis confirmed MRSA. Laboratory markers indicated severe sepsis with leukocytosis of 34,840 /mm³ and hyperglycemia of 328 mg/dL. Following acute stabilization and surgical debridement, the patient sustained a complex soft-tissue defect crossing multiple aesthetic subunits. A staged reconstruction was performed three weeks post-debridement. A V-Y advancement flap was utilized for the infraorbital and medial cheek defects to minimize ectropion risk, while a rotation flap was designed for the glabella and nasal dorsum to recruit forehead tissue. Conclusion: The combination of V-Y advancement and rotation flaps provides a robust, anatomically adaptable, and aesthetically superior solution for complex midfacial defects where skin laxity is compromised. This approach allows for tension-free closure in the aesthetic subunits of the face, even in patients with compromised perfusion due to diabetes. Early recognition of MRSA in diabetic vestibulitis is critical to preventing catastrophic tissue loss.